2014
DOI: 10.1515/epoly-2014-0049
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated fluorinated-aromatic polymers as proton exchange membranes

Abstract: Abstract:In recent years, extensive research on the preparation and properties of proton exchange membranes (PEMs) has been realized. This article focusses on the recent studies on new PEM materials based on aromatic hydrocarbon polymers with sulfonated groups as hydrophilic domains and fluorinated groups as hydrophobic domains as alternatives to conventional perfluorinated polymers. It is necessary to improve the proton conductivity especially under low-humidity conditions and at high operating temperatures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 94 publications
1
55
0
Order By: Relevance
“…In PEMs, water uptake, swelling ratio, mechanical property, proton conductivity, and oxidative stability are directly related to the phase separation between the hydrophilic and hydrophobic domains of the membrane . The phase morphology of the PTHQSH‐XX membranes was studied by scanning transmission electron microscopy (STEM), and the micrographs are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In PEMs, water uptake, swelling ratio, mechanical property, proton conductivity, and oxidative stability are directly related to the phase separation between the hydrophilic and hydrophobic domains of the membrane . The phase morphology of the PTHQSH‐XX membranes was studied by scanning transmission electron microscopy (STEM), and the micrographs are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…This element also helps in increasing chemical and thermal stability while decreasing the crystallinity and water absorption of the polymers . Furthermore, fluorine helps in the formation of phase separated morphology, which significantly improved the proton conductivity . Therefore, many efforts have been made in the recent years to prepare fluorinated sulfonated copolymer membranes with good proton conductivity and suitable dimensional stability .…”
Section: Introductionmentioning
confidence: 99%
“…The interconnection of the ionic clusters gradually increases with DS that eventually helps in better proton transport (47). The TEM micrographs showed small ionic clusters (20-35 nm) membranes form good microphaseseparated morphol ogy, because of the presence of highly hydrophobic 6F moieties in the polymer backbone (36,42).…”
Section: Microstructural Analysismentioning
confidence: 99%
“…[21][22][23][24][25][26] The prepared polymers showed a good set of physical properties, e.g., high thermal and mechanical stability as well as high dimensional and oxidative stability relative to many other polyimides. [27,28] However, much work is still required in designing new polytriazoles with high proton conductivity. In our continued research on development of PEM materials, we observed that simple structural manipulation of the diamines resulted in polyimides with an altogether different set of physical properties.…”
Section: Introductionmentioning
confidence: 99%